LITERATURE SURVEY AND RECOMMENDATIONS FOR SUKUK RESEARCH DIRECTIONS - Indri Supriani; Laila Masruro Pimada; Deni Kurniawan; Pusvita Yuana; Rihana Sofie Nabella; Sri Muljaningsih (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
Sukuk have emerged as a significant alternative source of funding, gaining recognition as a safe-haven investment instrument that attracts considerable attention from both practitioners and academics. This research aims to evaluate the current state of Sukuk literature through a combination of quantitative and qualitative analyses. This study adopts a hybrid methodology. A bibliometric analysis is employed to identify the most influential institutions, authors, journals, and highly cited articles in the field. In addition, a Systematic Literature Review (SLR) approach was chosen to highlight the most frequently discussed topics in Sukuk-related literature, extract the main findings from previous studies, and propose possible directions for future research. Findings from previous studies suggest that educational institutions such as Malaysian and Indonesian universities are major contributors to Sukuk research. This study concludes that there are four thematic groups in the existing literature: (1). Sukuk as a Safe Investment Instrument Option in Islamic Financial Market; (2). Development of Sukuk in the Global Financial Market Industry; (3). Dynamics and Potential of Sukuk as an Investment Instrument; and (4). Comparison between Sukuk and Conventional Bonds. This study adds to the body of knowledge in academic research by encouraging collaboration between international institutions and researchers, thereby improving the quality of cross-country research on the topic of Sukuk. Furthermore, this study provides valuable insights for future researchers to fill some of the key research gaps that have not been explored.